Memaksimalkan nilai perusahaan: Struktur modal, penghindaran pajak, dan faktor moderasi - Rahmawati, Agustin Ike; Ardimansyah, Ardimansyah; Aryasa, Hence Made (Jurnal Manajemen, 2024)
This research aims to investigate the influence of capital structure and Tax Avoidance on firm value, with profitability as a moderating variable and firm size as a control variable. This study adopts a quantitative research approach, focusing on the population of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange. Using purposive sampling, a sample of 27 companies, equivalent to 135 research samples, was selected. Data were obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) and the respective company websites, as well as IDX statistics for the year 2020. The analytical techniques employed encompass descriptive analysis, classical assumption tests, multiple linear regression analysis, simultaneous test (F-test), partial test (t-test), coefficient of determination test, and moderation regression analysis (MRA), with the assistance of SPSS 18. The research findings indicate that the capital structure variable significantly influences firm value, while the Tax Avoidance variable does not significantly affect firm value. Additionally, the moderating variable of profitability significantly moderates the impact of capital structure and Tax Avoidance on firm value.